2019
DOI: 10.7759/cureus.6251
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of N-Acetylcysteine in Management of Tyrosine Kinase Inhibitor Induced Acute Liver Injury

Abstract: Tyrosine kinase inhibitors (TKIs) have been adopted in the treatment of a variety of malignancies. Despite their popularity, the underlying mechanism of the adverse effects seen with the use of TKIs is not completely understood. Acute liver injury is a known side effect of many of these drugs. Some papers have demonstrated that N-acetylcysteine may have a role in non-acetaminophen induced acute liver failure (NAI-ALF). There is little evidence supporting the use of N-acetylcysteine in the treatment of tyrosine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Meta-analysis indicated safety and limited benefit regarding prolongation of patient survival with native liver without transplantation and survival after transplantation however, with no improvement of overall survival [70] NAC significantly reduces the level of reactive oxygen species produced by sunitinib and crizotinib and reduces sunitinib-and crizotinib-induced mitochondrial apoptosis and cellular damage. The use of NAC has been reported in several case reports of fulminant acute liver failure associated with TKIs [17,[71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis indicated safety and limited benefit regarding prolongation of patient survival with native liver without transplantation and survival after transplantation however, with no improvement of overall survival [70] NAC significantly reduces the level of reactive oxygen species produced by sunitinib and crizotinib and reduces sunitinib-and crizotinib-induced mitochondrial apoptosis and cellular damage. The use of NAC has been reported in several case reports of fulminant acute liver failure associated with TKIs [17,[71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…In another study NAC together with prednisolone when used in cases of severe idiosyncratic DILI due to fupirtine (central acting non-opiod analgesic) showed a significant improvement in ALT, AST and INR within 2 weeks compared to those who were not treated with NAC ( Borlak et al, 2018 ). Furthermore, it is reported that NAC is benefit for tyrosine kinase inhibitors and norfloxacin-induced acute liver injury ( Elliott et al, 2016 ; Patel et al, 2019 ). As shown in a prospective controlled study by an American ALF research group, which was conducted in 24 medical centers for 8 years in 173 patients with ALF caused by non-APAP agents, NAC could improve the survival rate of patients who were at the early stage of DILI-related ALF and had not undergone liver transplantation ( Lee et al, 2009 ).…”
Section: Pharmacotherapy Strategiesmentioning
confidence: 99%
“…14 In general, these effects show NAC may be a useful agent to preserve liver function in patients with biliary obstruction, which was the path for glutathione production. 15…”
Section: Introductionmentioning
confidence: 99%